Positive electrode pre-dispersion liquid and positive electrode slurry for lithium secondary battery containing same
Patent Information
- Application Number
- CN202280003982.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-05
- Filing Date
- 2022-04-19
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-04-19
AI Technical Summary
然而,不可逆添加剂结构不稳定,并且随着二次电池的充电的进行可能按如下产生大量氧气(O2),并且在正极中使用高含量的不可逆添加剂在锂二次电池的充电和放电效率以及安全性方面存在局限性:
[0059]根据本发明的锂二次电池正极用预分散液含有高含量的由化学式1表示的正极添加剂,并且通过在测量UV-Vis吸光度时调整在特定波长范围内存在的峰的面积比例,不仅正极添加剂在正极浆料中的分散性和工作性得到改善,而且在正极浆料中所含的正极添加剂的损失最少的同时,能够抑制在正极浆料制备过程中可能产生的副反应,从而具有使用所述正极浆料制造的电极的电性能优异的优点。
Smart Images

Figure CN115701778B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a pre-dispersion liquid for positive electrodes and a positive electrode slurry containing the same for lithium secondary batteries.
[0002] This application claims priority based on Korean Patent Application No. 10-2021-0071268 filed on June 2, 2021 and Korean Patent Application No. 10-2022-0042281 filed on April 5, 2022, and incorporates the entire contents disclosed in the documents of the aforementioned Korean patent applications as part of this specification. Background Technology
[0003] With the technological advancements and increasing demands of mobile devices, the need for secondary batteries as an energy source is rapidly growing. Among these secondary batteries, lithium-ion batteries, characterized by high energy density and operating potential, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0004] Recently, as lithium secondary batteries have been used as power sources for medium and large-sized devices such as electric vehicles, there is a further need for lithium secondary batteries with high capacity, high energy density and low cost, and even higher irreversible capacity for the irreversible additives used in the electrodes.
[0005] To address this need, conventional irreversible additives such as Li6CoO4 have been developed. However, irreversible additives are structurally unstable and may generate large amounts of oxygen (O2) as the secondary battery is charged. Furthermore, the use of high concentrations of irreversible additives in the cathode has limitations in terms of charging and discharging efficiency and safety of lithium secondary batteries.
[0006]
[0007] Therefore, efforts have been made to improve the irreversibility of lithium-ion batteries by using low amounts of irreversible additives. However, when irreversible additives are used in low amounts, especially in small quantities of less than 5% by weight based on the total weight of the cathode slurry, the problem is that not only is it difficult to ensure dispersion in the cathode slurry and the electrical performance of the lithium-ion battery is reduced, but the freedom of process design is also reduced due to the increased dispersion and loss of low-particle-size irreversible additives during cathode manufacturing.
[0008] Therefore, there is a need for a technology that can ensure the electrical performance of lithium secondary batteries by ensuring the dispersion of irreversible additives in the cathode slurry when using irreversible additives.
[0009] [Related Technical Documents]
[0010] [Patent Literature]
[0011] Korean Patent Publication No. 10-2018-0023696 Summary of the Invention
[0012] [Technical Issues]
[0013] Therefore, the object of the present invention is to provide a positive electrode slurry and a positive electrode for a lithium secondary battery manufactured using the same, wherein the positive electrode slurry contains a very small amount of irreversible additives that have high dispersibility and are not lost during the manufacture of the positive electrode.
[0014] [Technical Solution]
[0015] To address the aforementioned problems, in one embodiment, the present invention provides a pre-dispersion liquid for a lithium secondary battery positive electrode, the pre-dispersion liquid containing a positive electrode additive represented by the following chemical formula 1, a first conductive material, and a binder:
[0016] [Chemical Formula 1]
[0017] Li p Co (1-q) M 1 q O4
[0018] in,
[0019] M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0020] p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0021] In this case, the first conductive material may include one or more selected from the following: natural graphite, artificial graphite, carbon nanotubes, graphene, acetylene black, carbon black, Ketjen black, and carbon fiber.
[0022] Furthermore, the first conductive material may include one or more of carbon nanotubes and graphene.
[0023] In addition, based on 100 parts by weight of solids content, the pre-dispersion may contain 0.5 to 30 parts by weight of positive electrode additive, 20 to 85 parts by weight of first conductive material and 20 to 70 parts by weight of binder.
[0024] In addition, the cathode additive can have a tetragonal structure with space group P42 / nmc.
[0025] Furthermore, when UV / Vis absorbance is measured in the wavelength range of 350 to 800 nm, the area of the peak appearing in the pre-dispersion in the wavelength range of 560 to 680 nm can account for more than 50% of the total peak area.
[0026] Furthermore, when analyzing the CIE LAB color coordinates of the pre-dispersion liquid, one or more of 20≤L and b≤20 can be satisfied.
[0027] Furthermore, in one embodiment, the present invention provides a method for preparing a pre-dispersion liquid for a lithium secondary battery cathode, the method comprising the following steps:
[0028] A pre-dispersion is prepared by mixing a positive electrode additive represented by the following chemical formula 1, a first conductive material, and a binder:
[0029] [Chemical Formula 1]
[0030] Li p Co (1-q) M 1 q O4
[0031] in,
[0032] M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0033] p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0034] In this case, the step of preparing the pre-dispersion liquid can be carried out at a temperature below 40°C and a relative humidity below 10%.
[0035] Furthermore, when UV / Vis absorbance is measured in the wavelength range of 350 to 800 nm, the area of the peak appearing in the pre-dispersion in the wavelength range of 560 to 680 nm can account for more than 50% of the total peak area.
[0036] Furthermore, in one embodiment, the present invention provides a positive electrode slurry for lithium secondary batteries, the positive electrode slurry comprising a positive electrode active material, the aforementioned positive electrode pre-dispersion liquid, and a second conductive material.
[0037] Here, the positive electrode active material may comprise a lithium metal composite oxide represented by the following chemical formula 2:
[0038] [Chemical Formula 2]
[0039] Li x [Niy Co z Mn w M 2 v O u
[0040] wherein
[0041] M 2 is at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and
[0042] x, y, z, w, v and u are respectively 1.0≤x≤1.30, 0≤y<0.95, 0<z≤0.5, 0<w≤0.5, 0≤v≤0.2 and 1.5≤u≤4.5.
[0043] Based on 100 parts by weight of the solid content of the positive electrode slurry, the content of the positive electrode active material may be 60 wt% to 99 wt%.
[0044] In addition, based on 100 parts by weight of the solid content of the positive electrode slurry, the content of the second conductive material may be 0.5 to 5 parts by weight.
[0045] In addition, the second conductive material may include one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and carbon fiber.
[0046] Furthermore, in one embodiment, the present invention provides a method for preparing a positive electrode slurry for a lithium secondary battery, the method comprising the following steps:
[0047] preparing a pre-dispersion by mixing a positive electrode additive represented by the following Chemical Formula 1, a first conductive material and a binder; and
[0048] preparing a positive electrode slurry by mixing a positive electrode active material and a second conductive material with the prepared pre-dispersion;
[0049] wherein when the UV / Vis absorbance is measured in the wavelength range of 350 to 800 nm, the area of the peak of the pre-dispersion appearing in the wavelength range of 560 to 680 nm accounts for more than 50% of the total peak area,
[0050] [Chemical Formula 1]
[0051] Li p Co (1-q) M 1 q O4
[0052] wherein
[0053] M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0054] p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0055] Here, the steps for preparing the positive electrode slurry may include:
[0056] An active material mixture is prepared by mixing a positive electrode active material and a second conductive material under atmospheric pressure; and
[0057] The positive electrode slurry is prepared by mixing the prepared active material mixture and the pre-dispersed liquid under vacuum conditions.
[0058] [Beneficial Effects]
[0059] The pre-dispersed solution for the positive electrode of a lithium secondary battery according to the present invention contains a high content of positive electrode additive represented by chemical formula 1. By adjusting the area ratio of peaks present in a specific wavelength range when measuring UV-Vis absorbance, not only is the dispersibility and workability of the positive electrode additive in the positive electrode slurry improved, but also the loss of the positive electrode additive contained in the positive electrode slurry is minimized while the side reactions that may occur during the preparation of the positive electrode slurry are suppressed. Thus, the electrode made using the positive electrode slurry has the advantage of excellent electrical performance.
[0060] Furthermore, because pre-dispersion liquids for lithium secondary battery cathodes can directly detect the dispersibility of cathode additives and whether side reactions occur during the preparation of cathode slurry, they have the advantage of being applicable to product quality control (QC). Attached Figure Description
[0061] Figure 1 These are photographs showing the appearance of the predispersants prepared in Example 3 and Comparative Example 5. Detailed Implementation
[0062] Because the present invention can have many variations and multiple implementation schemes, specific implementation schemes will be described in detail in the detailed description.
[0063] However, this is not intended to limit the invention to specific embodiments, and should be understood to include all variations, equivalents and alternatives included within the spirit and scope of the invention.
[0064] In this invention, it should be understood that the terms "comprising" or "having" are intended to explicitly state the presence of the described features, numbers, steps, operations, components, elements or combinations thereof, but do not exclude the presence or addition of one or more other features or numbers, steps, operations, components or combinations thereof.
[0065] Furthermore, in this invention, when a portion of a layer, film, region, plate, etc., is described as being "above" another portion, it includes not only the case where the portion is "directly above" the other portion, but also the case where other portions are present in between. Conversely, when a portion of a layer, film, region, plate, etc., is described as being "below" another portion, this includes both the case where other portions are present in between and the case where the portion is "directly below" the other portion. Additionally, in this document, "above" can refer not only to being positioned above the top, but also to being positioned above the bottom.
[0066] In this invention, "color coordinates" refers to coordinates in the CIE Lab color space, which are color values defined by the International Commission on Illumination (CIE). Any position in the CIE color space can be represented by three coordinate values L*, a*, and b*.
[0067] Here, the L* value represents brightness; when L* = 0, it represents black, and when L* = 100, it represents white. Furthermore, the a* value indicates whether the color at the corresponding color coordinate leans towards pure magenta or pure green, and the b* value indicates whether the color at the corresponding color coordinate leans towards pure yellow or pure blue.
[0068] Specifically, the range of a* values is -a* to +a*, with the maximum value (a*max) representing pure magenta and the minimum value (a*min) representing pure green. For example, a negative a* value indicates a color leaning towards pure green, and a positive value indicates a color leaning towards pure magenta. When comparing a* = 80 and a* = 50, this means that a* = 80 is closer to pure magenta than a* = 50. Similarly, the range of b* values is -b* to +b*. The maximum value (b*max) represents pure yellow, and the minimum value (b*min) represents pure blue. For example, a negative b* value indicates a color leaning towards pure blue, and a positive value indicates a color leaning towards pure yellow. When comparing b* = 50 and b* = 20, this means that b* = 50 is closer to pure yellow than b* = 20.
[0069] Furthermore, in this invention, "solid content" refers to the weight percentage of solid material remaining after removing the solvent, based on the initial weight of the pre-dispersion or cathode slurry for lithium secondary battery cathodes according to the invention. For example, when the weight of solid material remaining after removing the solvent from 1 kg of cathode slurry is 500 g, the solid content of the cathode slurry is 50%.
[0070] Furthermore, in this invention, "Ah" is a unit of capacity for lithium secondary batteries, referred to as "ampere-hour," and refers to the current flow rate per hour. For example, when the battery capacity is "3000mAh," it means that the battery can discharge at a current of 3000mA for 1 hour.
[0071] The invention will be described in more detail below.
[0072] Predispersant for positive electrode of lithium secondary battery
[0073] In one embodiment, the present invention provides a pre-dispersion liquid for a lithium secondary battery positive electrode, the pre-dispersion liquid containing a positive electrode additive represented by the following chemical formula 1, a first conductive material, and a binder:
[0074] [Chemical Formula 1]
[0075] Li p Co (1-q) M 1 q O4
[0076] in,
[0077] M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0078] p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0079] The pre-dispersion for the positive electrode of a lithium secondary battery according to the present invention contains a positive electrode additive, a first conductive material, and a binder, and may not contain a positive electrode active material. When it contains a positive electrode active material, its content based on 100 parts by weight of solids can be 20 parts by weight or less. The pre-dispersion for the positive electrode according to the present invention improves the reduction in measurement accuracy relative to the positive electrode additive and thus improves the deterioration of workability, while preventing the loss of the positive electrode additive caused by using a fine-particle positive electrode additive in an amount of less than 5 parts by weight based on 100 parts by weight of solids in the positive electrode slurry during preparation.
[0080] Here, the positive electrode additive can be a lithium cobalt oxide represented by the following chemical formula 1:
[0081] [Chemical Formula 1]
[0082] Li p Co (1-q) M 1 q O4
[0083] in,
[0084] M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0085] p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0086] The positive electrode additive can contain excess lithium to provide lithium for the lithium consumed at the negative electrode due to irreversible chemical and physical reactions during the initial charging, thereby increasing the battery's charging capacity and reducing irreversible capacity to improve lifespan characteristics.
[0087] The cathode additive represented by Formula 1 has a higher lithium-ion content than commonly used nickel-containing oxides in the art, thereby replenishing lithium-ions lost due to irreversible reactions during the initial activation of the battery, and thus significantly improving the battery's charging and discharging capacity. Furthermore, compared to commonly used iron-containing oxides and / or manganese-containing oxides in the prior art, the battery does not experience side reactions due to the dissolution of transition metals during charging and discharging, thus exhibiting excellent battery stability. The lithium metal oxide represented by Formula 1 may include Li6CoO4, Li6Co... 0.5 Zn 0.5 O4, Li6Co 0.7 Zn 0.3 O4, etc.
[0088] Furthermore, the cathode additive represented by Formula 1 can have a tetragonal crystal structure, wherein it can be contained in the P42 / nmc space group having a twisted tetrahedral structure formed by cobalt and oxygen elements. Because the cathode additive has a twisted tetrahedral structure formed by cobalt and oxygen elements, it is structurally unstable and may undergo side reactions with moisture and / or oxygen in the air at temperatures exceeding 40°C and / or relative humidity exceeding 10% (RH). However, the advantage of this invention is that by pre-dispersing the cathode additive, side reactions with moisture or oxygen in the air can be prevented.
[0089] Furthermore, the first conductive material is used to improve the electrical performance of the positive electrode, and materials commonly used in the art can be applied. Specifically, one or more carbon-based materials selected from natural graphite, artificial graphite, carbon nanotubes, graphene, carbon black, acetylene black, Ketjen black, and carbon fiber can be used. For example, carbon nanotubes or graphene can be used alone or in combination as the first conductive material.
[0090] Furthermore, the adhesive serves to bind the positive electrode active material, positive electrode additive, and conductive material together; as long as it possesses this function, it can be used without particular restrictions. Specifically, the adhesive may include one or more resins selected from: polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, and copolymers thereof. For example, the adhesive may include polyvinylidene fluoride.
[0091] Furthermore, the pre-dispersion for the positive electrode may contain a positive electrode additive, a first conductive material, and a binder in a predetermined proportion based on the solid content. Specifically, based on 100 parts by weight of solid content, the pre-dispersion for the positive electrode may contain 0.5 to 30 parts by weight of the positive electrode additive, 20 to 85 parts by weight of the first conductive material, and 20 to 70 parts by weight of the binder.
[0092] For example, based on the solid content of 100 parts by weight of the pre-dispersion for cathode, the content of the cathode additive can be 0.5 to 20 parts by weight, 0.5 to 18 parts by weight, 0.5 to 15 parts by weight, 0.5 to 10 parts by weight, 0.5 to 5 parts by weight, 0.5 to 3 parts by weight, 5 to 20 parts by weight, 10 to 20 parts by weight, 11 to 20 parts by weight, 20 to 30 parts by weight, or 8 to 16 parts by weight.
[0093] As another example, based on the solid content of 100 parts by weight of the pre-dispersion liquid for the positive electrode, the content of the first conductive material can be 20 to 75 parts by weight, 20 to 70 parts by weight, 20 to 65 parts by weight, 20 to 50 parts by weight, 20 to 45 parts by weight, 25 to 40 parts by weight, 30 to 75 parts by weight, 35 to 75 parts by weight, 45 to 75 parts by weight, 50 to 75 parts by weight, 60 to 75 parts by weight, 25 to 65 parts by weight, 70 to 75 parts by weight, or 31 to 40 parts by weight.
[0094] As another example, based on the solid content of 100 parts by weight of the pre-dispersion for the positive electrode, the content of the binder can be 20 to 60 parts by weight, 20 to 45 parts by weight, 20 to 30 parts by weight, 20 to 25 parts by weight, 25 to 60 parts by weight, 25 to 45 parts by weight, 25 to 30 parts by weight, 30 to 60 parts by weight, 40 to 75 parts by weight, or 45 to 55 parts by weight.
[0095] Furthermore, the predispersant for the positive electrode may also contain a dispersion medium for dispersing the positive electrode additive, the first conductive material, and the binder. Examples of dispersion media include one or more polar aprotic solvents such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), acetonitrile (ACN), acetone, ethyl acetate, and distilled water. For example, the dispersion medium may contain N-methyl-2-pyrrolidone (NMP), in which case not only can the viscosity of the predispersant be easily adjusted, but the evaporation rate of the solvent can also be appropriately controlled so that the mixture layer does not crack due to rapid solvent evaporation during the manufacturing of the positive electrode.
[0096] Furthermore, the pre-dispersion for the positive electrode according to the present invention can exhibit a specific color, specifically a blue color.
[0097] For example, when measuring the UV / Vis absorbance of the pre-dispersion according to the invention in the wavelength range of 350–800 nm, the area of the peak appearing in the wavelength range of 560–680 nm can account for more than 50% of the total peak area; specifically, it can account for more than 60%, 65%, 70%, 75%, 80%, 85%, or 90% of the total peak area. Light with a wavelength of 560–680 nm is yellow and / or reddish-yellow light in the visible spectrum, and the pre-dispersion according to the invention can absorb light with a wavelength of 560–680 nm and reflect blue as its complementary color.
[0098] As another example, the pre-dispersion for the positive electrode can satisfy one or more of the conditions 20≤L and b≤20 when analyzing CIE LAB color coordinates; more specifically, it can satisfy 25≤L and b≤10; or, it can satisfy one or more of the conditions 30≤L≤80 and -80≤b≤10.
[0099] As described above, the pre-dispersion for lithium-ion secondary battery cathodes according to the present invention not only improves the dispersibility of cathode additives in cathode slurry by controlling the peak area ratio of UV / Vis absorbance and CIE LAB color coordinates, but also suppresses possible side reactions during cathode slurry manufacturing while minimizing the loss of cathode additives contained in the cathode slurry. Therefore, it can further improve the electrical performance in cathode slurries and lithium-ion secondary batteries containing the pre-dispersion. Moreover, because the pre-dispersion for lithium-ion secondary battery cathodes allows for direct detection of the dispersibility of cathode additives and the occurrence of side reactions during cathode slurry preparation, it has the advantage of being applicable to product quality control (QC) processes.
[0100] Method for preparing pre-dispersion liquid for lithium secondary batteries
[0101] Furthermore, in one embodiment, the present invention provides a method for preparing a pre-dispersion for a lithium secondary battery cathode, the method comprising preparing the pre-dispersion by mixing a cathode additive represented by the following chemical formula 1, a first conductive material, and a binder:
[0102] [Chemical Formula 1]
[0103] Li p Co (1-q) M 1 q O4
[0104] in,
[0105] M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0106] p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0107] Here, the preparation of the pre-dispersion involves mixing the positive electrode additive, conductive material, and binder, and can be carried out according to conventional methods used in the art for preparing slurries. For example, the pre-dispersion preparation step can be performed by adding the components to a homogenizer and stirring at 1000 to 5000 rpm for 30 to 600 minutes, and the viscosity can be controlled by adding solvent during stirring. For example, for the positive electrode pre-dispersion according to the invention, the positive electrode additive, conductive material, and binder represented by Formula 1 are introduced into a homogenizer, and N-methylpyrrolidone solvent is injected while mixing at 3000 rpm for 60 minutes to prepare a solution with a viscosity adjusted to 7500 ± 300 cps at 25 ± 1 °C.
[0108] Furthermore, the preparation of the pre-dispersion liquid can be carried out under specific temperature and humidity conditions to prevent the decomposition and / or damage of structurally unstable cathode additives.
[0109] Specifically, the step of preparing the pre-dispersion liquid can be carried out at temperatures below 40°C, more specifically at temperatures of 10°C to 40°C, 10°C to 35°C, 10°C to 30°C, 10°C to 25°C, 10°C to 20°C, 15°C to 40°C, 20°C to 40°C, 15°C to 35°C, or 18°C to 30°C.
[0110] Furthermore, the preparation of the pre-dispersion liquid can be carried out under relative humidity (RH) conditions of less than 10%, more specifically, under relative humidity (RH) conditions of less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, less than 3%, less than 2%, or less than 1%.
[0111] In this invention, by controlling the temperature and / or humidity conditions as described above during the preparation of the pre-dispersion for the positive electrode, the positive electrode additive in particulate form will not undergo side reactions with moisture and oxygen in the air during the mixing process with the first conductive material, thereby preventing irreversible degradation of activity.
[0112] Positive electrode slurry for lithium secondary batteries
[0113] Furthermore, in one embodiment, the present invention provides:
[0114] A positive electrode slurry for lithium secondary batteries, the positive electrode slurry comprising a positive electrode active material, the aforementioned positive electrode pre-dispersion liquid, and a second conductive material.
[0115] The positive electrode slurry for lithium secondary batteries according to the present invention is a composition for manufacturing the positive electrode used in lithium secondary batteries, and contains a positive electrode active material, a positive electrode additive, and a second conductive material. By including the pre-dispersed solution for positive electrodes of the present invention as a positive electrode additive, not only is a small amount of positive electrode additive uniformly dispersed in the slurry, but the activity of the positive electrode additive is also superior to that of positive electrode additives that are usually used in the form of fine particles. Therefore, the electrical performance of the positive electrode and the lithium secondary battery containing it can be improved.
[0116] Here, the positive electrode active material is a positive electrode active material capable of reversible insertion and extraction, and may include lithium metal composite oxides represented by the following chemical formula 2:
[0117] [Chemical Formula 2]
[0118] Li x [Ni y Co z Mn w M 2 v O u
[0119] in,
[0120] M 2 It is at least one element selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0121] x, y, z, w, v and u are respectively 1.0≤x≤1.30, 0≤y<0.95, 0<z≤0.5, 0<w≤0.5, 0≤v≤0.2 and 1.5≤u≤4.5.
[0122] The lithium metal composite oxide represented by Chemical Formula 2 is a composite metal oxide containing lithium and nickel, and may include one or more compounds selected from the following: LiCoO₂, LiCo 0.5 Zn 0.5 O₂, LiCo 0.7 Zn 0.3 O₂, LiNiO₂, LiNi 0.5 Co 0.5 O₂, LiNi 0.6 Co 0.4 O₂, LiNi 1 / 3 Co 1 / 3 Al 1 / 3 O₂, LiMnO₂, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O₂, LiNi 0.8 Co 0.1 Mn 0.1 O₂, LiNi 0.6 Co 0.2 Mn 0.2 O₂, LiNi 0.9 Co 0.05 Mn 0.05 O₂, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O₂ and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O₂.
[0123] For example, as the lithium metal composite oxide represented by Chemical Formula 2 contained in the positive electrode active material, LiNi may be used alone or in combination 1 / 3 Co 1 / 3 Mn 1 / 3 O₂, LiNi 0.8 Co 0.1 Mn 0.1 O₂, LiNi 0.6 Co 0.2 Mn 0.2 O₂, LiNi 0.8 Co 0.1 Mn 0.05 Al 0.05 O₂ or LiNi 0.6 Co 0.2Mn 0.15 Al 0.05 O2.
[0124] In addition, based on the total solids content of 100 parts by weight of the positive electrode slurry, the content of the positive electrode active material can be 80 to 99.5 parts by weight, specifically 85 to 95 parts by weight, 85 to 90 parts by weight, 90 to 95 parts by weight, or 86 to 95 parts by weight.
[0125] At this point, a second conductive material can be used to improve the properties of the positive electrode, such as conductivity. This second conductive material can be one or more carbon-based materials selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fiber. For example, carbon black or acetylene black can be used alone or in combination as the conductive material.
[0126] Furthermore, based on 100 parts by weight of the solid content of the positive electrode slurry, the content of the second conductive material can be 0.5 to 5 parts by weight, specifically 0.5 to 3 parts by weight or 0.5 to 2 parts by weight.
[0127] In this invention, by using the second conductive material in the positive electrode slurry together with the first conductive material contained in the pre-dispersion liquid for the positive electrode, a conductive network can be formed in the positive electrode slurry, thereby further improving the electrical performance of the manufactured positive electrode.
[0128] Method for preparing positive electrode slurry for lithium secondary batteries
[0129] Furthermore, in one embodiment, the present invention provides a method for preparing the above-mentioned positive electrode slurry for lithium secondary batteries.
[0130] Specifically, the preparation method includes the following steps:
[0131] A pre-dispersion is prepared by mixing a positive electrode additive represented by the following chemical formula 1, a first conductive material, and a binder; and
[0132] A positive electrode slurry is prepared by mixing the positive electrode active material and the second conductive material with the prepared pre-dispersion.
[0133] [Chemical Formula 1]
[0134] Li p Co (1-q) M 1 q O4
[0135] in,
[0136] M 1It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0137] p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0138] Here, the preparation of the pre-dispersion involves mixing the positive electrode additive, the first conductive material, and the binder, and can be carried out according to conventional methods used in the art for preparing slurries. For example, the pre-dispersion preparation step can be performed by adding the components to a homogenizer and stirring at 1000 to 5000 rpm for 30 to 600 minutes, and the viscosity can be controlled by adding solvent during stirring. For example, for the positive electrode pre-dispersion according to the invention, the positive electrode additive, conductive material, and binder represented by Formula 1 are introduced into a homogenizer and mixed at 3000 rpm for 60 minutes while N-methylpyrrolidone solvent is injected to prepare a solution with a viscosity adjusted to 7500 ± 300 cps at 25 ± 1 °C.
[0139] Furthermore, the preparation of the pre-dispersion liquid can be carried out under specific temperature and humidity conditions to prevent the decomposition and / or damage of structurally unstable cathode additives.
[0140] Specifically, the step of preparing the pre-dispersion liquid can be carried out at temperatures below 40°C, more specifically at temperatures of 10°C to 40°C, 10°C to 35°C, 10°C to 30°C, 10°C to 25°C, 10°C to 20°C, 15°C to 40°C, 20°C to 40°C, 15°C to 35°C, or 18°C to 30°C.
[0141] Furthermore, the preparation of the pre-dispersion liquid can be carried out under relative humidity (RH) conditions of less than 10%, more specifically, under relative humidity (RH) conditions of less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, less than 3%, less than 2%, or less than 1%.
[0142] In this invention, by controlling the temperature and / or humidity conditions as described above during the preparation of the pre-dispersion for the positive electrode, the particulate positive electrode additive will not undergo side reactions with moisture and oxygen in the air during the mixing process with the first conductive material, thereby preventing irreversible deterioration of activity.
[0143] For example, the prepared pre-dispersion can exhibit a specific color, specifically, a blue hue, by reducing the side reactions between the positive electrode additive and moisture and / or oxygen present in the air.
[0144] Therefore, in the pre-dispersion, when the UV / Vis absorbance of the pre-dispersion according to the invention is measured in the wavelength range of 350–800 nm, the area of the peak appearing in the wavelength range of 560–680 nm can account for more than 50% of the total peak area, specifically, it can account for more than 60%, 65%, 70%, 75%, 80%, 85%, or 90% of the total peak area. Light with a wavelength of 560–680 nm is yellow and / or reddish-yellow light in the visible spectrum, and the pre-dispersion according to the invention can absorb light with a wavelength of 560–680 nm and reflect blue as its complementary color.
[0145] Furthermore, the pre-dispersion solution for the positive electrode can satisfy one or more of the conditions 20≤L and b≤20 when analyzing CIE LAB color coordinates; more specifically, it can satisfy 25≤L and b≤10; or, it can satisfy one or more of the conditions 30≤L≤80 and -80≤b≤10.
[0146] Furthermore, the method for preparing the positive electrode slurry according to the present invention includes preparing the positive electrode slurry by mixing a positive electrode active material and a second conductive material in a pre-dispersion liquid.
[0147] The above steps involve mixing the positive electrode active material with the prepared pre-dispersion. There are no particular limitations on this mixing process, as long as it is a method commonly used in the art. However, specifically, it can be carried out by adding the positive electrode active material and the second conductive material together to the pre-dispersion. In some cases, it can be carried out by preparing a separate dispersion containing the positive electrode active material and the second conductive material and then mixing the prepared dispersion with the prepared pre-dispersion.
[0148] For example, the steps of preparing the positive electrode slurry may include: preparing an active material mixture by mixing the positive electrode active material with a second conductive material under atmospheric pressure; and preparing the positive electrode slurry by mixing the prepared active material mixture with a pre-dispersion liquid under vacuum conditions.
[0149] Specifically, in the step of preparing the active material mixture, the positive electrode active material and the second conductive material are mixed at atmospheric pressure (i.e., 1 atm) for 40 to 80 minutes to prepare an active material mixture containing the positive electrode active material, and the prepared active material mixture and the pre-prepared pre-dispersion liquid can be mixed under vacuum for 10 to 50 minutes to prepare a positive electrode slurry.
[0150] Here, by mixing the active material mixture and the pre-dispersion liquid under vacuum conditions, the side reactions between the positive electrode additive contained in the pre-dispersion liquid and moisture and / or oxygen in the air can be minimized.
[0151] Positive electrode for lithium secondary batteries
[0152] Furthermore, in one embodiment, the present invention provides a positive electrode for a lithium secondary battery, the positive electrode comprising:
[0153] Positive current collector; and
[0154] A positive electrode mixture layer is located on the positive electrode current collector and is prepared using the aforementioned positive electrode slurry.
[0155] The positive electrode for a lithium secondary battery according to the present invention comprises a positive electrode mixture layer manufactured by coating a positive electrode slurry onto a positive electrode current collector and then drying and pressing it, and the positive electrode mixture layer has a structure containing a positive electrode active material, a positive electrode additive represented by chemical formula 1, a conductive material and a binder.
[0156] In this case, the positive electrode mixture layer has the advantage of excellent electrical performance when prepared by using the positive electrode slurry of the present invention described above.
[0157] Furthermore, there are no particular limitations on the average thickness of the cathode mixture layer, and it can specifically be 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.
[0158] Furthermore, in the positive electrode, a current collector with high conductivity that will not cause chemical changes in the battery can be used. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc., can be used, and in the case of aluminum or stainless steel, materials with surfaces treated with carbon, nickel, titanium, silver, etc., can be used. In addition, to improve the adhesion of the positive electrode active material, fine irregularities can be formed on the surface of the positive electrode current collector, and various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics are feasible. Furthermore, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the current collector can be appropriately applied within the range of 3 to 500 μm.
[0159] Lithium secondary batteries
[0160] Furthermore, in one embodiment, the present invention provides a lithium secondary battery comprising: the positive electrode described above according to the present invention; a negative electrode; and a separator located between the positive electrode and the negative electrode.
[0161] The lithium secondary battery according to the present invention has a structure comprising the positive electrode according to the present invention as described above, a negative electrode, and a separator interposed between the positive electrode and the negative electrode. Since the lithium secondary battery is provided with the above positive electrode of the present invention to effectively replenish lithium ions lost due to irreversible reactions during the initial charging process, high capacity and long service life can be achieved in the subsequent charging and discharging processes of the battery.
[0162] Herein, the negative electrode is prepared by coating a negative electrode active material on a negative electrode current collector, followed by drying and pressing, and if necessary, may optionally further contain a conductive material, an organic binder polymer, additives and the like as in the positive electrode.
[0163] Further, as the negative electrode active material, for example, it is possible to use: graphite having a completely layered crystal structure such as natural graphite, as well as soft carbon and graphite materials having a layered crystal structure with low crystallinity (graphene structure; a structure in which hexagonal honeycomb planes of carbon are arranged in layers) such as hard carbon, artificial graphite, expanded graphite, carbon fibers, non-graphitizable carbon, carbon black, carbon nanotubes, fullerenes, activated carbon and the like, in which carbon and these structures are mixed with amorphous portions; metal composite oxides such as Li x Fe₂O₃ (0≤x≤1), Li x WO₂ (0≤x≤1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups 1, 2 and 3 of the Periodic Table of the Elements and halogens; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄ and Bi₂O₅; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxide; lithium titanium oxide and the like.
[0164] For example, the negative electrode active material may comprise both graphite and silicon (Si)-containing particles, and the graphite comprises at least one of natural graphite having a layered crystal structure and artificial graphite having an isotropic structure, and the silicon (Si)-containing particles may comprise particles mainly containing silicon (Si) as a metal component, for example, silicon (Si) particles, silicon oxide (SiO₂) particles, or a mixture of silicon (Si) particles and silicon oxide (SiO₂) particles.
[0165] At this point, based on a total of 100 parts by weight, the negative electrode active material can contain 80 to 95 parts by weight of graphite and 1 to 20 parts by weight of silicon (Si) particles. By adjusting the content of graphite and silicon (Si) particles in the negative electrode active material to the above range, this invention can increase the charging capacity per unit mass while reducing lithium consumption and irreversible capacity loss during the initial charging / discharging of the battery.
[0166] In addition, the average thickness of the negative electrode mixture layer can be from 100 μm to 200 μm, specifically from 100 μm to 180 μm, 100 μm to 150 μm, 120 μm to 200 μm, 140 μm to 200 μm, or 140 μm to 160 μm.
[0167] Furthermore, there are no particular restrictions on the negative electrode current collector, as long as it has high conductivity without causing chemical changes in the battery. Materials such as copper, stainless steel, nickel, titanium, and calcined carbon can be used, and in the case of copper or stainless steel, materials with surface treatments such as carbon, nickel, titanium, or silver can be used. In addition, similar to the positive electrode current collector, the negative electrode current collector can have fine irregularities formed on its surface to enhance the bonding force with the negative electrode active material, and can take various forms such as films, sheets, foils, meshes, porous materials, foams, and nonwoven materials. Furthermore, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector can be appropriately applied within the range of 3 to 500 μm.
[0168] Furthermore, a separator is inserted between the negative and positive electrodes, and an insulating film with high ion permeability and mechanical strength is used. While there are no particular limitations on the separator as long as it is commonly used in the art, specifically, sheets or nonwoven fabrics made of chemically resistant and hydrophobic polypropylene; glass fiber; polyethylene, etc., can be used. In some cases, composite separators in which inorganic / organic particles are coated onto a porous polymer substrate such as a sheet or nonwoven fabric using an organic binder polymer can be used. When a solid electrolyte, such as a polymer, is used as the electrolyte, the solid electrolyte can also serve as the separator. Furthermore, the average pore size of the separator can be from 0.01 to 10 μm, and the average thickness can be from 5 to 300 μm.
[0169] On the other hand, the positive and negative electrodes can be wound and housed in a cylindrical, prismatic, or pouch-shaped battery in the form of a jelly roll, or they can be housed in a pouch-shaped battery in a folded or stacked and folded form, but are not limited thereto.
[0170] Furthermore, the lithium-containing electrolyte according to the present invention can be composed of an electrolyte and a lithium salt, and as the electrolyte, non-aqueous organic solvents, organic solid electrolytes, inorganic solid electrolytes, etc. can be used.
[0171] As non-aqueous organic solvents, aprotic organic solvents such as N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triphosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, or ethyl propionate can be used.
[0172] As organic solid electrolytes, materials such as polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate-lysine, polyester sulfides, polyvinyl alcohol, polyvinylidene fluoride, and polymer materials containing ion-dissociating groups can be used.
[0173] As an inorganic solid electrolyte, nitrides, halides, sulfates, etc. of Li can be used, such as Li3N, LiI, Li5Ni2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.
[0174] The lithium salt is a material that is readily soluble in the non-aqueous electrolyte, and can be, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylic acids, lithium tetraphenylborate, lithium imide, etc.
[0175] In addition, to improve charge / discharge characteristics, flame retardancy, etc., substances such as pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoryltriamine, nitrobenzene derivatives, sulfur, quinone imine dyes, and N-substituted substances can be added to the electrolyte. Examples of electrolytes include azole ketones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, and aluminum trichloride. In some cases, to impart non-flammability, the electrolyte may also contain halogenated solvents such as carbon tetrachloride and trifluoroethylene, and may also contain carbon dioxide gas to improve high-temperature storage properties, and may also contain fluoroethylene carbonate (FEC), propylene sulfonate lactone (PRS), etc.
[0176] Preferred implementation scheme
[0177] The present invention will be described in detail below through examples.
[0178] However, the following embodiments and experimental examples are only used to illustrate the present invention, and the content of the present invention is not limited to the following embodiments and experimental examples.
[0179] Examples 1 to 3 and Comparative Examples 1 to 5: Preparation of predispersants for lithium secondary battery cathodes
[0180] Li6Co prepared as a cathode additive 0.7 Zn 0.3 O4, carbon nanotubes as the first conductive material and PVdF (weight-average molecular weight (Mw): 500,000 ± 25,000) as the binder, were weighed as shown in Table 1 and placed in a homogenizer. The mixture was then mixed at 2000 rpm for 30 minutes to prepare a pre-dispersion for the positive electrode of a lithium secondary battery. At this time, the mixing temperature and humidity were adjusted as shown in Table 1.
[0181] [Table 1]
[0182]
[0183] Examples 4 to 6 and Comparative Examples 6 to 10: Manufacturing of positive electrodes for lithium secondary batteries
[0184] LiNi is prepared as a positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 and carbon black, used as a second conductive material, were weighed as shown in Table 2, placed in a homogenizer, and N-methylpyrrolidone solvent was injected. The mixture was stirred at 2500 rpm for 60 minutes under atmospheric pressure (1 atm) to prepare an active material mixture. The prepared mixture, the positive electrode pre-dispersion prepared in Examples 1 to 3 and Comparative Examples 1 to 5, and the carbon black, used as a second conductive material, were weighed as shown in Table 2, placed in a homogenizer, and N-methylpyrrolidone solvent was injected. The mixture was then first mixed at 2500 rpm for 60 minutes. A second mixing was then performed under vacuum at 2500 rpm for 30 minutes to prepare a positive electrode slurry for lithium-ion batteries.
[0185] [Table 2]
[0186]
[0187] Comparative Example 11: Manufacturing of the positive electrode for lithium secondary batteries
[0188] N-methylpyrrolidone solvent was injected into a homogenizer, and 92 parts by weight of LiNi were weighed as the positive electrode active material. 0.6 Co 0.2 Mn 0.2 O2, 0.85 parts by weight of Li6Co as a positive electrode additive 0.7 Zn 0.3 O4, 3.08 parts by weight of carbon nanotubes as the first conductive material, 1 part by weight of acetylene black as the second conductive material, and 3.08 parts by weight of PVdF (weight average molecular weight (Mw): 500000±25000) as a binder were placed in a homogenizer and then mixed at 3000 rpm for 60 minutes to prepare the positive electrode slurry.
[0189] Experimental Example 1: Evaluation of Predispersant for Positive Electrode
[0190] To evaluate the performance of the pre-dispersion solution used in the positive electrode of lithium secondary batteries, the following experiments were conducted.
[0191] A) Measurement of UV / Vis absorbance
[0192] The color of the predispersants prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was observed with the naked eye. Then, the light absorption spectrum of the predispersants was measured in the wavelength range of 350 to 800 nm using UV-Vis spectroscopy. The peak area (A), the total peak area in the wavelength range of 560 to 680 nm (B), and the area of the strongest peak in the wavelength range of 560 to 680 nm (C) were calculated respectively. The total area ratio of peaks present in the wavelength range of 560 to 680 nm (B / A×100) and the area ratio of the strongest peak (C / A×100) were also calculated and are shown in Table 3 below.
[0193] B) Measurement of CIE LAB color coordinates
[0194] The color coordinates of the predispersants prepared in Examples 1 to 3 and Comparative Examples 1 to 5 in the CIE LAB color space were measured using a colorimeter, and the results are shown in Table 3 below.
[0195] [Table 3]
[0196]
[0197] As shown in Table 3, it was confirmed that the pre-dispersion for the cathode according to the present invention appears blue to the naked eye, and that when the UV / Vis absorbance was measured, the peak area in the wavelength range of 560 to 680 nm was greater than 50% of the total peak area, and the coordinates in the CIE LAB space satisfied 20 ≤ L and b ≤ 20. On the other hand, it was confirmed that the pre-dispersion of the comparative example was black or a near-black blue, and did not satisfy the conditions for UV / Vis absorption peaks and CIE LAB color space coordinates.
[0198] Experimental Example 2: Evaluation of Lithium Secondary Batteries
[0199] The positive electrode slurry prepared in Examples 4 to 6 and Comparative Examples 6 to 11 was coated on one side of an aluminum current collector, dried at 100°C, and rolled to produce a positive electrode. At this time, the total thickness of the positive electrode mixture layer was 130 μm, and the total thickness of the manufactured positive electrode was approximately 200 μm.
[0200] In addition, natural graphite and silicon (SiOx, condition 1≤x≤2) particles were prepared as the negative electrode active material, and styrene-butadiene rubber (SBR) was prepared as the binder. Referring to Tables 1 and 2, the negative electrode slurry was prepared in the same manner as the positive electrode slurry. Here, the graphite used to prepare the negative electrode mixture layer was natural graphite (average particle size: 0.01 to 0.5 μm), and silicon (SiOx) particles with an average particle size of 0.9 to 1.1 μm were used. The prepared negative electrode slurry was coated onto one side of a copper current collector, dried at 100°C, and calendered to manufacture the negative electrode. At this point, the total thickness of the negative electrode mixture layer was 150 μm, and the total thickness of the manufactured negative electrode was approximately 250 μm.
[0201] Then, a separator made of porous polyethylene (PE) membrane (thickness: about 16 μm) is inserted between the manufactured positive and negative electrodes, and E2DVC as electrolyte is injected to manufacture a battery in the form of a full cell.
[0202] Here, "E2DVC" is a carbonate electrolyte and refers to a solution obtained by mixing lithium hexafluorophosphate (LiPF6, 1.0M) and ethylene carbonate (VC, 2% by weight) in a mixture of ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio).
[0203] To evaluate the performance of the cathode additive according to the present invention, the following experiments were conducted using the lithium secondary battery cell prepared therefrom.
[0204] A) Measurement of oxygen production during charging and discharging
[0205] For lithium secondary batteries manufactured using the cathode slurry of the examples and comparative examples, initial charging (formation) was performed at 55°C under conditions of 3.5V and 1.0C, and the gas generated at the cathode was degassed during the initial charging to analyze the oxygen content generated during the initial charging process. Then, the batteries were repeatedly charged and discharged 50 times at 0.3C and 45°C to further analyze the oxygen content generated due to electrolyte decomposition during each charge / discharge cycle, and the analysis results are shown in Table 4 below.
[0206] B) Evaluation of the charge / discharge capacity and retention rate of lithium secondary batteries
[0207] For lithium secondary batteries manufactured using the cathode slurry of the examples and comparative examples, they were charged at 25°C with a charging current of 0.1C to a charging cutoff voltage of 4.2 to 4.25V, and then charged until the current density at the cutoff voltage was 0.01C for activation. They were then discharged with a discharge current of 0.1C to a cutoff voltage of 2V, and the initial charge / discharge capacity per unit mass was measured.
[0208] Then, while repeatedly charging and discharging 50 times at 45°C and 0.3C, the charge and discharge capacity were measured, and the charge / discharge capacity retention rate was calculated after 50 charge and discharge cycles. The results are shown in Table 4 below.
[0209] [Table 4]
[0210]
[0211] As shown in Table 4, it can be seen that the lithium secondary battery manufactured using the positive electrode pre-dispersion of the present invention produces less oxygen after initial charging / discharging and has excellent initial charging / discharging capacity and excellent capacity retention.
[0212] Specifically, the lithium secondary battery of the embodiment generates 80 to 110 ml / g of oxygen during the initial charging and discharging, and it was found that the amount of oxygen generated during subsequent charging and discharging processes is significantly reduced. This means that the small amount of positive electrode additive contained in the positive electrode mixture layer has high irreversible activity and is uniformly dispersed, thus participating in most of the irreversible reactions during the initial charging and discharging processes. Furthermore, it was found that the lithium secondary battery of the embodiment exhibits an initial charging and discharging capacity of over 103 Ah and a high capacity retention rate of over 91%, indicating that the positive electrode additive contained in the positive electrode mixture layer has high irreversible activity, thereby effectively replenishing the lithium ions lost due to the irreversible reactions during the initial charging and discharging processes.
[0213] These results show that the pre-dispersion for cathode according to the present invention contains a high content of cathode additive represented by chemical formula 1, and has the following structure: the area ratio of peaks existing in a specific wavelength range is controlled in UV-Vis absorbance measurement, thereby not only improving the dispersibility of cathode additive in cathode slurry and its workability in cathode slurry preparation, but also suppressing possible side reactions during cathode slurry manufacturing while minimizing the loss of cathode additive during cathode slurry manufacturing, thereby maintaining the high activity of cathode additive.
[0214] Although the invention has been described above with reference to preferred embodiments thereof, it should be understood by those skilled in the art or of ordinary skill in the art that various changes and variations can be made thereto without departing from the spirit and scope of the invention as set forth in the following claims.
[0215] Therefore, the technical scope of this invention should not be limited to the content described in the detailed description of the specification, but should be defined by the claims.
Claims
1. A pre-dispersion for a positive electrode of a lithium secondary battery, the pre-dispersion comprising a positive electrode additive represented by the following Chemical Formula 1, a first conductive material, and a binder, wherein, based on 100 parts by weight of the solid content, the pre-dispersion contains 0.5 to 30 parts by weight of the positive electrode additive, 20 to 85 parts by weight of the first conductive material, and 20 to 70 parts by weight of the binder, wherein when UV / Vis absorbance is measured in the wavelength range of 350 to 800 nm, the area of the peak appearing in the wavelength range of 560 to 680 nm accounts for 50% or more of the total peak area, [Chemical Formula 1] Li p Co (1-q) M 1 q O4 wherein, M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and p and q are respectively 5≤p≤7 and 0≤q≤0.
5.
2. The pre-dispersion according to claim 1, wherein the first conductive material comprises one or more selected from the group consisting of natural graphite, artificial graphite, carbon nanotubes, graphene, carbon black, and carbon fibers.
3. The pre-dispersion according to claim 1, wherein the first conductive material comprises one or more of carbon nanotubes and graphene.
4. The pre-dispersion according to claim 1, wherein the positive electrode additive has a tetragonal structure with a space group of P4₂ / nmc.
5. The pre-dispersion according to claim 1, wherein when analyzing the CIE LAB color coordinates of the pre-dispersion, two or more of 0≤L, -30≤a≤30 and b≤20 are satisfied.
6. A method for manufacturing a pre-dispersion for a positive electrode of a lithium secondary battery, the method comprising the following step: preparing a pre-dispersion by mixing a positive electrode additive represented by the following Chemical Formula 1, a first conductive material, and a binder, wherein, based on 100 parts by weight of the solid content, the pre-dispersion contains 0.5 to 30 parts by weight of the positive electrode additive, 20 to 85 parts by weight of the first conductive material, and 20 to 70 parts by weight of the binder, wherein the step of preparing the pre-dispersion is performed at a temperature below 40°C. wherein the step of preparing the pre-dispersion is performed at a relative humidity of 10% or less. wherein when UV / Vis absorbance is measured in the wavelength range of 350 to 800 nm, the area of the peak of the pre-dispersion appearing in the wavelength range of 560 to 680 nm accounts for 50% or more of the total peak area, [Chemical Formula 1] Li p Co (1-q) M 1 q O4 wherein, M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and p and q are respectively 5≤p≤7 and 0≤q≤0.
5.
7. A positive electrode slurry for a lithium secondary battery, the positive electrode slurry comprising: a positive electrode active material; the pre-dispersion for a positive electrode according to claim 1; and a second conductive material.
8. The positive electrode slurry according to claim 7, wherein the positive electrode active material is a lithium metal composite oxide represented by the following Chemical Formula 2: [Chemical Formula 2] Li x [Ni y Co z Mr w M 2 v ]O u wherein, M 2 It is at least one element selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and x, y, z, w, v and u are respectively 1.0≤x≤1.30, 0≤y<0.95, 0<z≤0.5, 0<w≤0.5, 0≤v≤0.2 and 1.5≤u≤4.
5.
9. The positive electrode slurry according to claim 7, wherein based on 100 parts by weight of the solid content of the positive electrode slurry, the content of the positive electrode active material is 80 to 99.5 parts by weight.
10. The positive electrode slurry according to claim 7, wherein the content of the second conductive material is 0.5 to 5 parts by weight based on the solid content of 100 parts by weight of the positive electrode slurry.
11. The positive electrode slurry according to claim 7, wherein the second conductive material comprises one or more selected from natural graphite, artificial graphite, carbon black and carbon fiber.
12. A method for preparing a positive electrode slurry for lithium secondary batteries, the method comprising the following steps: A pre-dispersion is prepared by mixing a positive electrode additive represented by the following chemical formula 1, a first conductive material, and a binder; and A positive electrode slurry is prepared by mixing the positive electrode active material and the second conductive material with the prepared pre-dispersion liquid. Based on a solid content of 100 parts by weight, the pre-dispersion contains 0.5 to 30 parts by weight of the positive electrode additive, 20 to 85 parts by weight of the first conductive material, and 20 to 70 parts by weight of the binder. The step of preparing the pre-dispersion liquid is carried out at a temperature below 40°C. The step of preparing the pre-dispersion liquid is carried out at a relative humidity of less than 10%. When UV / Vis absorbance is measured in the wavelength range of 350 to 800 nm, the area of the peak appearing in the wavelength range of 560 to 680 nm of the pre-dispersion accounts for more than 50% of the total peak area. [Chemical Formula 1] Li p Co (1-q) M 1 q O4 in, M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
13. The method according to claim 12, wherein the step of preparing the positive electrode slurry comprises: An active material mixture is prepared by mixing a positive electrode active material and a second conductive material under atmospheric pressure. and The positive electrode slurry is prepared by mixing the prepared active material mixture and the pre-dispersed liquid under vacuum conditions.
Citation Information
Patent Citations
Method of fabricating secondary battery
KR1020180023696A
Waist gate valve for turbo charger
KR1020210071268A
Electronic sexually transmitted diseases kit
KR1020220042281A
Lithium titanate, manufacturing method therefor, slurry used in said manufacturing method, electrode active material containing said lithium titanate, and lithium secondary battery using said electrode active material
US20120261622A1
Secondary battery, positive electrode for secondary battery, and manufacturing method of positive electrode for secondary battery
US20210143404A1